Identification and analysis of cuproptosis associated molecular clusters and immunological profiles in atopic dermatitis - Wang, Liangzhe; Wang, Bo; Peng, Min; Yang, Xiaoyan; Huang, Sijia; Wang, Ruixin; Du, Lin; Yao, Ruiqian; Wang, Wei; Dong, Baiping; Zhu, Yuanjie (Frontiers in Immunology, 2025)
BackgroundAtopic dermatitis (AD) is a chronic skin condition marked by persistent itching and dryness. The role of cuproptosis, a novel form of programmed cell death, in AD is not yet understood.MethodsThe GSE107361 dataset was obtained from the Gene Expression Omnibus (GEO) database. Cuproptosis-related genes (CRGs) in AD were identified and analyzed, and immune landscape analysis was performed using ssGSEA. AD was clustered based on CRGs using ConsensusClusterPlus. Weighted gene co-expression network analysis (WGCNA) and differential gene expression analysis were conducted. Hub genes between AD clusters were identified, and both protein-protein interaction (PPI) and drug-gene interaction networks were developed.ResultsThree CRGs (DLD, MTF1, and GLS) were significantly upregulated in the AD group compared to healthy controls. Notably, four core CRGs (LIAS, LIPT1, PDHA1, CDKN2A) distinguished early-onset from adult-onset AD, indicating more active cuproptosis in early-onset AD. CRGs were linked to immune cell infiltration in AD, highlighting differences in immune microenvironments between early- and adult-onset AD. Early-onset AD showed high innate immunity, while adult-onset AD had a mix of innate and type 1 adaptive immunity. CRG expression identified two molecular subtypes with distinct immune infiltration: Cluster 2 (high cuproptosis) had predominant innate immunity, while Cluster 1 (low cuproptosis) had adaptive immunity. Additionally, 102 hub DEGs were identified through WGCNA co-expression network analysis, and 10 hub node genes were identified and potential drugs were explored for the management of AD.ConclusionsThe study provides insights into the roles of cuproptosis-related processes in the pathogenesis and potential treatment of AD. Finding of key hub genes between the 2 distinct immune infiltration subtypes might inform potential therapeutic strategies for AD.